Analysis of Supplier Selection of Plate Raw Material (Case Study: PT XYZ) - Dewie Saktia Ardiantono; Bustanul Arifin Noer; Dhea Elvira Rosa; M. Ubaidillah Al Mustofa (Jurnal Sosial Humaniora, 2019)
PT. XYZ is one of the State-Owned Enterprises of StrategicIndustries (BUMNIS) which runs the business field of Project Managementand Services (MPJ) and Machinery and Equipment Industry (MPI).Currently the company is experiencing problems of not achieving the salesgrowth target in 2012-2016. This problem is caused mainly by one of theproblems in supply chain, namely the delay of raw materials on the projectundertaken. From the results of previous study, it was found that supplierselection evaluation has the highest value of the total effectiveness to difficultyratio (ETDk); therefore, evaluation on supplier selection should be done inorder to establish good integration. The method used is Analytical HierarchyProcess. Criteria that have been determined is the price, delivery, quality, andservice. As a result, the sub criteria of price and quality compliance has thehighest value and the first supplier is the best supplier.